Copper water heat pipe applied for Stirling engine - Ana Carolina Santos; Lamartine Nogueira Frutuoso Guimarães; Valéria Serrano Faillace Oliveira Leite (Brazilian Journal of Radiation Sciences, 2022)
Power generation in remote locations requires the advancement of efficient and long-lasting power generation technologies. One possible solution is a microreactor, which uses heat pipes to transport fission heat from a nuclear source to Stirling engines producing energy. In this context, TERRA (Advanced Fast Reactor Technology) project conducted by the Institute for Advanced Studies (IEAv) developed a Stirling engine and copper-water heat pipes for an initial study of both coupled devices. However, before using a nuclear source, it is necessary to understand the thermal behavior of the devices using an electrical heating source. Thus, the objective of this work is to test experimentally if a copper heat pipe can carry the necessary heat to activate the Free Piston Stirling engine. For this, it was necessary to develop a copper adapter to connect the pipe to the engine. The pipe was connected to the engine and temperatures were collected using T-thermocouples. The results of the experiments showed that the heat pipe was able to transport 28 W to the Stirling engine, which ran continuously. The maximum heat pipe temperatures were 253°C and the Stirling engine ran at 212°C in the hot source. Therefore, it was demonstrated that the IEAv´s copper-water heat pipe is capable of conducting the necessary heat to activate the IEAv´s Stirling engine and produce electricity. The results will form the basis for the future application of a nuclear source.